Analysis of Public Service Quality at PDAM Tirta Nusa Office of Natuna District, Indonesia - R. Rafita; Diani Indah; Ipah Ema Jumiati (Manunggal Halim Jaya, 2026)
Clean water services are a vital component of public services that significantly influence community quality of life, especially in archipelagic regions such as Natuna Regency, which face infrastructural limitations and geographical dispersion. This study aims to examine public service quality in clean water provision at PDAM Tirta Nusa, analyze service performance, and identify inhibiting factors. The study is based on the SERVQUAL framework by Parasuraman, Zeithaml, and Berry, encompassing tangibles, reliability, responsiveness, assurance, and empathy. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Data were analyzed using an interactive model. The findings reveal that service quality is relatively adequate but not yet optimal, particularly in water distribution continuity, responsiveness to customer complaints, and limited distribution facilities. Key obstacles include limited human resources, inadequate infrastructure, and geographical constraints. The study recommends strengthening institutional capacity, improving infrastructure, and enhancing service management.